ANTIOXIDANT CAPACITY AND TOTAL PHENOL CONTENT OF HYPTIS SPP., P. HEPTAPHYLLUM, T. PANAMENSIS, T. RHOIFOLIA, AND OCOTEA SP. (2015)
In this work, the possible correlation between the antioxidant activities and the Total Phenolic Content (TPC) and chemical composition of Lamiaceae (H. conferta, H. dilatata, H. mutabilis, H. suaveolens), Burseraceae (P. heptaphyllum, T. rhoifoila, T. panamensis), and Lauraceae (Ocotea sp.) were evaluated. The Trolox Equivalent Antioxidant Capacity or the Total Antioxidant Activity (TAA) was determined by using a colorimetric assay with the ABTS radical cation, Effective Concentration (EC50) was evaluated with the DPPH radical, and the TPC was established by the Folin-Ciocalteu method, for ethanolic extracts obtained by cold maceration and evaporation to dryness. Both the TAA and the EC50 were highly correlated with the TPC. The barks of T. rhoifolia and T. panamensis demonstrated the highest antioxidant capacities. The Burseraceae spp. exhibited the highest TPC, and the Lamiaceae (Hyptis spp.) demonstrated the lowest TPC.